Analysis of Lungs Maturity Induction (LMI) in Preterm Labor on Neonatal Asphyxia Status at dr. Sayidiman Regional General Hospital, Magetan (International Journal of Advanced Health Science and Technology, 2026)
Neonatal asphyxia remains a major contributor to neonatal morbidity and mortality, particularly among preterm infants whose lungs are physiologically immature and lack adequate surfactant production. At Dr. Sayidiman Regional General Hospital, Magetan, neonatal mortality due to asphyxia remains considerably high, indicating the need for effective preventive interventions. Lungs Maturity Induction (LMI) is widely recommended for pregnant women at risk of preterm delivery to accelerate fetal lung development; however, evidence regarding its effectiveness in reducing neonatal asphyxia in local clinical settings is still limited. This study aimed to analyze differences in neonatal asphyxia status among preterm births between mothers who received LMI and those who did not. This research employed an analytical survey with a cross-sectional design. Secondary data were obtained from the Delivery Register Book at Dr. Sayidiman Regional General Hospital, Magetan, covering the period from January 2024 to February 2025. The study population comprised 121 preterm deliveries, from which 93 samples were selected using proportional random sampling. Of these, 44 mothers received LMI and 49 did not. Neonatal asphyxia status served as the dependent variable, while LMI administration was the independent variable. Data were analyzed using the Chi-Square test with a significance level of α = 0.05. The results showed that 79.5% of preterm infants whose mothers received LMI did not experience neonatal asphyxia, whereas 75.5% of preterm infants without LMI experienced asphyxia. Statistical analysis demonstrated a significant difference in neonatal asphyxia status between the two groups (χ² = 26.090; p < 0.001). In conclusion, LMI is significantly associated with a lower incidence of neonatal asphyxia in preterm deliveries. The routine administration of LMI to pregnant women at risk of preterm birth is strongly recommended to improve neonatal outcomes and reduce neonatal mortality.